Surface acoustic wave driven microfluidics - Luong, Trung-Dung (2012)
This paper presents a systematic overview on the recent works on surface acoustic wave (SAW) driven microfluidics. SAW microfluidics is based on acoustic streaming induced by leaky SAW radiation into a liquid. The development of this field attracts attention from microfluidic research community due to its rapid actuation, programmable capability, simple and yet efficient operation. In our paper, SAW microfluidic applications are categorized into droplet-based applications and continuous-flow applications. Droplet is actuated into unique behaviours depending on the applied SAW power. A wide range of droplet based applications have been employed utilizing these behaviours. In continuous-flow system, applications are further categorized based on the interaction of travelling SAW and standing SAW with the bulk liquid. Finally, future perspectives of SAW driven microfluidics are discussed.